2023
DOI: 10.21608/dusj.2023.291027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Utilizing Glass Powder with Silica Fume on Mechanical Properties and Microstructure of Concrete

Abstract: Carbon dioxide (CO2) emissions from cement production and pollution from glass shards both contribute to critical environmental issues. To help in the elimination environmental issues, solid wastes like glass are used as a partial cement alternative. Glass powder is marked by an altitude level of silicon dioxide SiO2 in its chemical composition, which qualifies it as a pozzolanic material. Partial cement substitution with glass powder in silica fume concrete was explored, and the results have been compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…They must be able to resist those loads, derived from high speeds winds, vibrations, seismic activity, varying loading regimes (from compression to tension) and frequencies, as well as their own weight and the mechanical system, sustaining the nacelle, rotors and blades (Bošnjaković et shown that the improvement of the modulus of cementitious materials used in aerogenerator towers and foundations can lead to signi cant improvements in durability. As reported by literature, the use of silica fume (SF) in concrete can signi cantly enhance its compressive strength and elastic modulus, essential properties in those applications (Fattouh & Elsayed, 2023;Keerio et al, 2022;Boukhelf et al, 2021). Kuo & Zhuang (2021) also presented evaluations on high-performance concrete for aerogenerators foundations.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…They must be able to resist those loads, derived from high speeds winds, vibrations, seismic activity, varying loading regimes (from compression to tension) and frequencies, as well as their own weight and the mechanical system, sustaining the nacelle, rotors and blades (Bošnjaković et shown that the improvement of the modulus of cementitious materials used in aerogenerator towers and foundations can lead to signi cant improvements in durability. As reported by literature, the use of silica fume (SF) in concrete can signi cantly enhance its compressive strength and elastic modulus, essential properties in those applications (Fattouh & Elsayed, 2023;Keerio et al, 2022;Boukhelf et al, 2021). Kuo & Zhuang (2021) also presented evaluations on high-performance concrete for aerogenerators foundations.…”
Section: Introductionmentioning
confidence: 94%
“…With respect to SCMs, Silica fume (SF) and glass powder (GP) are considered by literature as two effective materials for improving the properties of cementitious materials, by replacing content of the ordinary Portland cement (OPC), with a signi cant focus on binder optimizations by its incorporation (Fattouh & Elsayed, 2023;Singh & Arora, 2023;Boukhelf et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects collectively lead to the enhancement of concrete durability. In general, using Silica Fume in the construction sector has been found to enhance the microstructure, densify the concrete, and enhance its strength and durability (Fattouh & Elsayed, 2023;Uzbas & Aydin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits which have been observed from such solutions include limiting the width of the initial microcracks in concretes of this type, reduction of porosity of such materials, and improving their mechanical parameters [37][38][39]. In most cases, however, such effects resulted from strengthening the cement matrix structure through the development of additional C-S-H and C-A-S-H phases [40][41][42]. Previous studies have shown, among other things, that a particularly positive effect on the microstructure of the ITZ area between coarse aggregate and paste is the modification of the composition of the cement binder with single additives and nanoadditives, such as:…”
mentioning
confidence: 99%